INVENTORY CONTROL ANALYSIS USING KANBAN AND JUNBIKI MODELS - Herawan, Fredi; Setiafindari, Widya (Jurnal Disprotek, 2024)
The development of many companies in Indonesia requires good and disciplined management, particularly in inventory control. PT XYZ has experienced inefficiency and ineffectiveness due to inventory buildup. The problems stem from employees performing double jobs, leading to production delays and increased storage costs, which have caused the company to incur losses. This research analyzes and evaluates the effectiveness of two inventory control methods, kanban and junbiki, aiming to determine which method is more effective in minimizing inventory control issues. The kanban production system involves creating the necessary kanban cards, calculating the number of kanbans required, planning an efficient kanban flow, and providing supporting facilities for the system. There are two commonly used types of kanban: withdrawal kanban and production order kanban. The junbiki method (JIT) is a production system designed to meet customer needs on time and in the desired quantity. The just in time (JIT) production system is implemented to avoid overproduction. Based on the kanban method calculations, the required number of kanban is two workers, whereas the junbiki method calculations require three workers. The comparison results show that the kanban method reduces labor by one worker or 50%, and reduces the area size by 574 mÂ² or 88%. Therefore, it can be concluded that the kanban method is more effective and efficient than junbiki, as it occupies a smaller area of 4357.1 mÂ², thus saving work process time, labor, and costs incurred.